2017
DOI: 10.1055/s-0036-1597258
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Treatment Approaches for Spoken Word Production in Aphasia

Abstract: This article provides an overview of phonological treatment approaches for anomia in individuals with aphasia. The role of phonology in language processing, as well as the impact of phonological impairment on communication is initially discussed. Then, traditional phonologically based treatment approaches, including phonological, orthographic, indirect, guided, and mixed cueing methods, are described. Collectively, these cueing treatment approaches aim to facilitate word retrieval by stimulating residual phono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Phonologically based treatments use different methods that collectively aim to facilitate word retrieval by stimulating residual phonological representation and strengthening the phonological representation of the word [ 111 ]. Typically, in the phonological treatment a target picture is shown and a hierarchy of phonological cueing is applied using rhyming cues, first phoneme cues, and/or first syllable cues [ 111 , 112 ]. Moreover, the cueing phonological hierarchy treatment can include different tasks, such as spontaneous naming, written naming, notebook search, reading and repetition.…”
Section: Phonological And/or Orthographic Treatmentmentioning
confidence: 99%
“…Phonologically based treatments use different methods that collectively aim to facilitate word retrieval by stimulating residual phonological representation and strengthening the phonological representation of the word [ 111 ]. Typically, in the phonological treatment a target picture is shown and a hierarchy of phonological cueing is applied using rhyming cues, first phoneme cues, and/or first syllable cues [ 111 , 112 ]. Moreover, the cueing phonological hierarchy treatment can include different tasks, such as spontaneous naming, written naming, notebook search, reading and repetition.…”
Section: Phonological And/or Orthographic Treatmentmentioning
confidence: 99%
“…It has been suggested that this phonemic cueing treatment approach relies upon the same processes that underlie priming in unimpaired speakers ( Best et al , 2002 ; Nickels 2002 ), where phonemic cues prime the retrieval of a word’s correct phonological form ( Miceli et al , 1996 ; Starreveld, 2000 ). In aphasic patients, the hypothesis is that naming improvements using this treatment approach rely on recruitment and priming of residual ‘normal’ naming neural networks ( Madden et al , 2017 ). However, despite the longstanding use of phonemic cues to aid naming in clinical practice, surprisingly the neural mechanisms underlying this treatment approach have not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…Speech-language therapies developed to improve naming abilities in people with aphasia are numerous. Therapies aiming to reduce anomia are generally based on semantic strategies, such as Semantic Feature Analysis [ 17 , 18 ], or phonological strategies, such as Phonological Component Analysis PCA [ 19 , 20 , 21 , 22 , 23 ]. In phonological therapies, the aim is to facilitate lexical retrieval by increasing the activation of the phonological representation of words [ 24 ].…”
Section: Introductionmentioning
confidence: 99%